Significant factors of motivational needs that influence job satisfaction through regression analysis / Nur Izzah Jamil, Nor Aslily Sarkam and Amariah Hanum Hussin - Jamil, Nur Izzah; Sarkam, Nor Aslily; Hussin, Amariah Hanum (UiTM Press, 2020)
Motivation is an important life skill. Each person has purposes and to steward their purposes, it must be motivated to work towards their goals which can help their dreams become to reality. The higher the level of motivation needs, the higher the level of their job satisfaction. The main objective of this research is to identify motivational needs that influence the job satisfaction among respondents involved in this study. Specifically, to identify the relationship and significant variables between job satisfaction and five factors of motivational needs namely physiological needs, safety and security needs, love and belonging needs, self-esteem needs, and self-actualization needs. A sample of respondents who were working and doing part-time study was taken from public and private universities in Malaysia using convenience sampling. Therefore, the result of this research cannot be inferred to the population as a whole and only valid to the respondents involved in this research. The data was analyzed by using Statistical Package Social Science (SPSS) software. Preliminary analysis was conducted such as reliability analysis. Furthermore, correlation analysis was used to quantify the associations between motivational needs and job satisfaction. Multiple linear regression was used to identify significant variables in the model. The results indicated that there was a significant positive linear relationship between motivational needs towards job satisfaction. Furthermore, safety and security, self-esteem and self-actualization made statistically significant contribution to the job satisfaction in the model.